Academic Anxiety of Vietnamese Secondary School Students as a Reason for Applying Online Learning - Ng, Phan Trong; Dung, Vu; Nguyet, Le Minh; Linh, Vu Thi Khanh; Thuy, Hoang Thanh; Tinh, Nguyen Thi (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Academic anxiety is one of the major problems in student psychology across the world. It applies equally to students of all ages, from elementary school to college and university students. Research shows that learning online is an effective way to defuse feelings of academic anxiety. Elimination of anxiety is clearly visible regardless of age, gender, or prior online learning experience. The study aims to identify academic anxiety as one of the most important reasons for moving to online learning or blended learning in secondary school. The study investigated academic anxiety among secondary school students in Vietnam. After surveying 677 students in classroom learning, the results showed that 13.7% of secondary students suffered from frequent anxiety, and 3.0% of them suffered from very frequent anxiety. Lower anxiety was observed among students actively participated in-class activities, and students with excellent academic performance. These factors can be optimally enhanced through blended and online learning. There were no differences in academic anxiety among male and female students, urban and rural students. There was a moderate correlation between a student’s anxiety level and pressure of the school, parental expectations, students’ motivation for high performance, and especially, among students who have the melancholic temperament. And the influence of these negative factors can also be optimally reduced with the help of online learning. Regression model could provide useful suggestions for parents, teachers and students in reducing academic anxiety for students, including the use of full or blended online learning.